Vulnerabilities of the Peruvian financial system - Pozo, Jorge (2014)
The purpose of this article is to present an analysis to identify the vulnerabilities of the financial system in order to reduce the probability of a financial crisis. The methodology proposed in Adrian et al. (2014) is followed. The article is organized as follows: The second section reviews the theoretical framework developed by Adrian et al. {2014), The third section presents the evaluation of some indicators that could be used to measure the vulnerabilities that could exist in the financial system. Finally, the fourth section concludes and gives some recommendations.